Optical characterization of grain orientation in crystalline materials - Gaskey, Bernard (2022)
Characterizing crystallographic orientation is essential for assessing structure-property relationships in crystalline solids. While diffraction methods have dominated this field, low throughput and high cost limit their applicability to small, specialized samples and restrict access to well-funded research institutions. We develop a complementary method that expands applicability and broadens access. We demonstrate crystal orientation mapping over centimeter-scale surfaces using nothing more than a conventional optical microscope and commercial laptop. Our approach relies on a novel analysis method that correlates crystal lattice orientation to optical reflectance of specially etched surfaces. We successfully apply the method to metal and semiconductor surfaces. The simplicity, low cost, and enhanced sample throughput of our method promise to expand the availability of crystallographic orientation mapping significantly, making it readily available in education as well as academic research and industrial settings.